Meta Analysis: Determinants of Dental Caries in Children - Siregar, Attila Yulaicha Advendila; Dewanti, Rosalia Indri; Khulwani, Qumara Wilda; Murti, Bhisma; Aqsyari, Riski (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Dental caries in children occurred when one or more teeth that are decayed (lesions), missing (due to caries), or filled tooth surfaces in primary teeth experienced by children. The aim of this study is to analyze the influence of dental caries factors in children based on the results of several previous studies using meta-analysis. Subjects and Method: This study is a systematic review and meta-analysis based on data obtained through various databases including Google Scholar and PubMed. This study used articles that were published from 2016 to 2022. The article search was carried out by considering the eligibility criteria defined using the PICO model. Population: children. Intervention of chocolate, candy, biscuits, soft drinks. Comparison: free sugar intake. Outcome: dental caries. This article was collected within 1 month with the following keywords used: